2018
DOI: 10.1016/j.cmet.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Lipid Metabolism Confers Antiangiogenic Drug Resistance

Abstract: Intrinsic and evasive antiangiogenic drug (AAD) resistance is frequently developed in cancer patients, and molecular mechanisms underlying AAD resistance remain largely unknown. Here we describe AAD-triggered, lipid-dependent metabolic reprogramming as an alternative mechanism of AAD resistance. Unexpectedly, tumor angiogenesis in adipose and non-adipose environments is equally sensitive to AAD treatment. AAD-treated tumors in adipose environment show accelerated growth rates in the presence of a minimal numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
184
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(191 citation statements)
references
References 42 publications
6
184
0
1
Order By: Relevance
“…However, a direct effect of iDGAT on tumor cells could not be excluded. Studies reported a potent role of lipid metabolism in the survival and drug resistance of cancer cells (Boroughs & DeBerardinis, ; Iwamoto et al , ). Thus, to specifically disrupt LD formation in myeloid cells in vivo , peptide modified liposomes served as delivery vehicle for iDGAT treatment () (Karathanasis et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…However, a direct effect of iDGAT on tumor cells could not be excluded. Studies reported a potent role of lipid metabolism in the survival and drug resistance of cancer cells (Boroughs & DeBerardinis, ; Iwamoto et al , ). Thus, to specifically disrupt LD formation in myeloid cells in vivo , peptide modified liposomes served as delivery vehicle for iDGAT treatment () (Karathanasis et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the abundance and close proximity of mammary adipose tissue (source of FAs) to breast cancer tumors, breast tumors rely on lipid metabolism to favor survival by increasing the expression of various proteins regulating lipid metabolism (68,69). This is evident by an upregulation of various enzymes catalyzing de novo FA synthesis in breast cancer cells i.e., Acetyl-CoA carboxylase (ACC), FAS and SCD-1 (13,70,71).…”
Section: Diet-induced Obesity Distinctly Alters Lipid Metabolism In Tmentioning
confidence: 99%
“…One example for this concept was demonstrated by a study showing that provision of lipids from the surrounding tissue blocks the effect of anti-angiogenic therapy on the growth of colorectal cancer cells (Iwamoto et al, 2018). In this system, high-fat-diet-induced liver steatosis augmented the protective effect, suggesting that diet can modulate therapeutic efficacy.…”
Section: You Are What You Eat: the Effect Of Diet On Cancer Cell Metamentioning
confidence: 99%